التصميم بمساعدة الحاسوب ونمذجة أسس نظام عمل محطة ضخ تعمل بتغذية كهربائية من خلايا شمسية - كفا, سمير نمر; النجار, رائد (Latakia University Journal -Engineering Sciences Series, 2019)
يقدم هذا البحث نموذج رياضي يصف العلاقة بين شدة الإشعاعات الشمسية من جهة و بين نظام عمل تجهيزات محطة ضخ المياه عند مختلف احتمالات تركيب الإدارة الكهربائية من جهة أخرى ، حيث جرى باستخدام الحاسب الآلي تحليل الأداء الوظيفي لمحطات الضخ الشمسية عند مختلف حالات توجيه الخلية الشمسية ، وذلك في أربع احتمالات مختلفة للإدارة الكهربائية ضمن الظروف المناخية للقطر العربي السوري ، واعتماداً على نظرية التدفق الأعظمي لتكامل مختلف الفترات الزمنية /في الساعة- اليوم- السنة/. وفي النهاية تم محاولة تعميم مواصفات المضخات النابذة المدارة من محرك كهربائي لا تزامني ، بحيث نستطيع تحديد بارامترات نظام عمل المضخة وعلاقتها بتغير بارامترات الخلية الشمسية. This paper provides a mathematical model for describing the relationship between the intensity of solar radiation on one hand and between the operating system of pumping station equipment in the different possibilities of electric circuit installation, on the other. We have used a computer to analyze the functional performance of solar pumping stations at various stages of directing the solar cell, namely in four different possibilities of the electrical circuit within the climatic conditions of Syrian Arab Republic taking into account the theory of maximum flow for the integration of different time periods /hour-day-year/. Finally, we have attempted to generalize the specifications of pumps not being run by a simultaneous electric engine. In so doing, we can specify the parameters of the pump operating system and its relationship with parametric changes of the solar cell.